SISTEM INFORMASI KEGIATAN PEKERJAAN FISIK PROGRAM DMIJ BERBASIS WEB STUDI KASUS DESA SUNGAI PIYAI KEC. KUALA INDRAGIRI - Ahmad Suprianto; Ilyas Ilyas; Samsudin Samsudin (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2020)
The problem that is often encountered in the reporting progress system is that village employees still often use consultant services to prepare DMIJ project reports, so they require additional costs for consulting services, not to mention the time required to complete so many DMIJ project reports. So that with the progress reporting information system and applications that will be designed, it can help the work process of village employees so that they no longer need consultant services in order to save budget costs and time. Then, the solution that expected for the web-based DMIJ physical work activity information system uses the Development Life System (SDLC) method, could help the employees in order to prepare the project report progress more quickly and precisely.